HUBUNGAN POLA ASUH ORANG TUA DENGAN PERKEMBANGAN SOSIAL ANAK RETARDASI MENTAL RINGAN PADA ANAK USIA 7-9 TAHUN DI SDLB BHAKTI LUHUR MALANG - Anil Masyayih , Warda; Siswati, Eny (LPPM STIKES HUSADA JOMBANG, 2022)
Mental retardation is a disability that often occurs in children. Mental retarded children show intellectual function and ability in adaptive behavior below their age so children who are mentally retarded are less able to develop the skills and habits of their children. Research Objectives To determine the relationship between parenting and social development of children with mild mental retardation in children aged 7-9 years at SDLB Bhakti Luhur Malang The research design used was correlational analytic research with a cross sectional design approach. Samples of Most Children Aged 7-9 Years in SDLB Bhakti Luhur Malang as many as 46 people using non-probability techniques: random sampling. The measuring instrument used was a questionnaire, the results of which were analyzed using the Spearman Rho test with a significance level of 5% (α = 0.05). The results of this study indicate that it can be known children who have parenting democracy and have good social development, as many as 28 respondents (60.8%), have parenting democracy and have enough social development namely as many as 12 respondents (26.1%), have parenting old democracy and have less social development that is as much as 1 respondent (2.1%). Whereas from the Spearman Rho test, the sig value was obtained. (2-tailed) or ρ value 0.001 (because ρ value <0.05) then the H0 is rejected and H1 is accepted. Based on the results of this study, it can be concluded that there is a relationship between Parental Parenting Patterns and Social Development of Mild Mental Retardation Children at the age of 7-9 years at SDLB Bhakti Luhur Malang. Spearman correlation coefficient of 0.001.